Media Pembelajaran Digital Berbasis Macromedia Flash untuk Mata Pelajaran Fisika tingkat SMP - Andinusa Rahmandhika; Heni Hendaryati; Ary Dwi Astuti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The development and improvement of teaching innovation aim to bring an enjoyable, joyful, active, and creative atmosphere for students to increase and improve their achievement. Teaching media that support student's creativity and critical thinking are needed to facilitate teachers presenting the learning material. Information and Communication Technology (ICT) can introduce media to increase students' learning motivation. This program instructs teachers in using Macromedia flash software to create learning media applications for the physics units. It was conducted in SMP Muhammadiyah 6 Dau Malang. An instrument to observe the teaching situation is an interview with the teacher. Information from the interview, students have high motivation during their practice in the lab, but the opposite occurs in the class. The result of this program is an attractive teaching media application created by using Macromedia Flash software.